Comparative A Model Islamic Constitution dalam Pembentukan Dual Yuridiction Yudikatif Pasca Amandemen UUD 1945 - Rahmat, Diding; Sarip, Sarip (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2019)
The Republic Indonesia has continually changed since reformation particularly regarding the institution that uphold national law. The historical process resulted in the formation of dual jurisdiction of the judiciary, namely the supreme court (MA) and the contitutional court (MK). Dual jurisdiction is interesting fact to be noticed. This model is used to analyze the problems of state administration. This article shows that the history of Indonesian governance has played significant role in Indonesian politics. Indonesian state administration is inseparable from the influence of A Model Islamic Contitution on the amendment. Hence, Indonesia is basically not an Islamic state but a country that adopts several Islamic constitutional provisions which are then adjusted to the Indonesian domain. This role has now been realized in a judicial institution namely the Constitutional Court of the Republic of Indonesia as the mandate of the 1945 amendment.